Branding Books Across the Ages Strategies and Key Concepts in Literary Branding - van den Braber, Helleke; Dera, Jeroen; Joosten, Jos; Steenmeijer, Maarten (Amsterdam University Press, 2021)
As marketing specialists know all too well, our experience of products is prefigured by brands: trademarks that identify a product and differentiate it from its competitors. This process of branding has hitherto gained little academic discussion in the field of literary studies. Literary authors and the texts they produce, though, are constantly 'branded': from the early modern period onwards, they have been both the object and the initiator of a complex marketing process. This book analyzes this branding process throughout the centuries, focusing on the case of the Netherlands. To what extent is our experience of Dutch literature prefigured by brands, and what role does branding play when introducing European authors in the Dutch literary field (or vice versa)? By answering these questions, the volume seeks to show how literary scholars can account for the phenomenon of branding.